Clinical value of serum miR‐92 and miR‐122 expression level combined with pulmonary ultrasound score in the prognosis of neonatal acute respiratory distress syndrome. Issue 7 (25th May 2022) - Hong, Haiyan; Fu, Binbin; Wang, Renyuan
Abstract: Purpose: To explore the value of the expression of serum miR‐92 and miR‐122 combined with lung ultrasound score (LUS) in the prognosis of neonatal acute respiratory distress syndrome (ARDS). Patients and methods: This study involved 148 neonatal ARDS cases from January 2018 to October 2021, of which 77 children were discharged from hospital and 31 died. The children with ARDS were classified according to disease severity based on X‐ray examination as mild ( n  = 69 cases) and severe ( n  = 39 cases). The expression of serum miR‐92 and miR‐122 was detected by real‐time fluorescence quantitative PCR and the LUS score was recorded. The data were subjected to ROC curve analysis and Pearson correlation analysis. Results: The expression of serum miR‐92, miR‐122, and LUS score in the patients that died were significantly higher than in those who survived ( p  < 0.05). These indicators were also significantly higher in the severe disease group compared to the mild disease group ( p  < 0.05). ROC curve showed that serum miR‐92 and miR‐122 combined with the LUS score had the largest area under the curve (0.920, 95% CI: 0.860–0.977) for predicting death, with a sensitivity and specificity of 92.0% and 87.0%, respectively. Pearson correlation analysis showed that the expression levels of serum miR‐92 and miR‐122 were positively correlated with the LUS score (all p  < 0.01). Conclusions: The increased expression of serum miR‐92 and miR‐122 is related to the severity and prognosis of children with ARDS, combined with the LUS score are of value to predict the prognosis of children with ARDS. Abstract : The increased expression of serum miR‐92 and miR‐122 is related to the severity and prognosis of children with ARDS and combined with the LUS score are of value to predict the prognosis of children with ARDS.